Bullying as a barrier to participation in inclusive education: integrating prevention into Ukraine’s school practices - Berghauer-Olasz Emőke; Бергхауер-Олас Емйовке; Greba Ildikó; Греба Ілдіко (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. This article conceptualises bullying as a systemic barrier to participation within Ukraine’s inclusive education. Drawing on 2024 – 2025 empirical studies and current guidance from the Ministry of Education and Science, we argue that formal placement without deliberate design of classroom interaction leaves learners with special educational needs (SEN) vulnerable to peer victimisation and subtler forms of social exclusion. We propose a participation-oriented prevention model that (1) embeds anti-bullying measures in each learner’s Individual Support Plan (ISP); (2) extends Universal Design for Learning (UDL) beyond access to the design of interaction (predictable turn-taking, rotating nonhierarchical roles, mixed-ability cooperation); (3) couples high academic expectations with warm, consistent teacher - student relationships; and (4) integrates peer support and social-emotional learning (SEL) within the base class. Evidence from inclusive classrooms indicates that such routines narrow status asymmetries, reduce opportunities for relational bullying, and strengthen belonging. At the whole-school level, routine monitoring, staff development, and coordinated engagement with families are required, particularly under hybrid and resource-uneven conditions typical of Ukrainian schools. Effective bullying prevention is therefore a necessary condition for meaningful participation of SEN learners in ordinary classes rather than an optional add-on.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: inclusive education; special educational needs (SEN); bullying prevention; participation; school climate; peer support; Universal Design for Learning (UDL); social-emotional learning (SEL)